Men's experiences of eating disorder treatment: A qualitative systematic review of men‐only studies. Issue 2 (23rd July 2020) - Richardson, Candice; Paslakis, Georgios
Accessible summary: What is known on the subject?: There is a widespread perception that eating disorders are predominantly women´s illnesses. Most studies in the field of eating disorders include predominantly women. Current eating disorder programmes are tailored to meet women´s needs. At the same time, studies show that the rate of eating disorders among men is rising. Men tend to seek help for their eating disorder late in the course of their illness; even when they do seek treatment, they run risk of being undiagnosed by health professionals. What the paper adds to existing knowledge?: We assessed the current knowledge on how men think and feel about their eating disorders and explored how this may affect their help‐seeking behaviours and how they go about managing their eating disorders. Men experience unique symptoms and issues that may translate into unique treatment needs. There is a call to re‐evaluate the current status quo for men with eating disorders regarding access to and receiving treatment for their eating disorders. What are the implications for practice?: It is becoming an increasing priority to effectively treat men with eating disorders. Men need to be recognized as stakeholders in eating disorder‐associated health care delivery. Healthcare professionals should receive training about the nature of eating disorders in men. Eating disorder‐specific treatments will require adaptations to mirror the needs of individuals rather than particular gender/sex entities. Abstract: Objective: Despite the widespread perception that eating disorders (EDs) are predominantly experienced by women and girls, the incidence rate among men has risen substantially in recent years. Men may face unique challenges accessing treatment, which can negatively affect prognosis. The present paper aimed to review men's thoughts and feelings about their ED, and their experiences of ED treatment. Method: We conducted a systematic search for qualitative articles focusing on the treatment experiences of men with EDs. Results: Nine studies met inclusion criteria. Key themes that emerged across the studies were as follows: (a) recognition of the ED, (b) help‐seeking, (c) treatment characteristics and (d) patient characteristics. Given that EDs are widely regarded to exclusively affect women and girls, men were reluctant to recognize their EDs, faced minimization of their symptoms by health professionals and had difficulty finding treatments that were tailored to their unique needs and preferences as men. Conclusions: The present findings may serve as reference points to design future ED‐specific interventions that are more inclusive of men. Further studies are needed to explore the differential experiences of men across diagnostic categories and treatment types, as well as elucidate the potential role of men‐only services.